A Re-Examination of the Monetary Model of Exchange Market Pressure: Canada, 1963-1988 - Burdekin, Richard C. K.; Burkett, Paul (The Review of Economics and Statistics, 1990)
Richard C. K. Burdekin, Paul Burkett, A Re-Examination of the Monetary Model of Exchange Market Pressure: Canada, 1963-1988, The Review of Economics and Statistics, Vol. 72, No. 4 (Nov., 1990), pp. 677-681